Incidence of interattack asymptomatic brain lesions in NMO spectrum disorder. (8th December 2020) - Lee, Min Young; Yong, Kok Pin; Hyun, Jae-Won; Kim, Su-Hyun; Lee, Sang-Hyun; Kim, Ho Jin
Abstract : Objective: To determine whether aquaporin-4 (AQP4) antibody–seropositive patients with neuromyelitis optica spectrum disorder (NMOSD) develop new asymptomatic brain lesions during the interattack period. Methods: Of 296 consecutive AQP4 antibody–seropositive patients in the NMOSD database of the National Cancer Center from May 2005 to November 2019, 145 patients, who had serial brain MRI scans over an interval of at least 1 year during relapse-free period after immunosuppressive therapy, with 370 longitudinally assessed brain MRI scans were included in this study. We retrospectively analyzed them for presence of new subclinical brain lesions during the relapse-free period. Results: Five of 145 patients (3.4%) had detectable new, asymptomatic brain lesions in the deep white matter over a total observed relapse-free period of 708 person-years. All the lesions were smaller than 6 mm and assessed to be nonspecific. No brain lesion characteristic of NMOSD or gadolinium-enhancing lesion was identified. Conclusions: Asymptomatic brain lesions are rarely observed on conventional MRI in clinically stable AQP4 antibody–seropositive patients with NMOSD after immunosuppressive therapy and brain MRI lesions characteristic of NMOSD are not seen in the relapse-free period. These findings may provide further insight regarding currently known diagnostic and disease-monitoring strategies in NMOSD.